Social resonance and the transformation of meaning of Gondang Sabangunan through arts education at SMK Negeri 11 Medan - Susilawaty P, Ezra; Widodo, Widodo; Syarif, Muh Ibnan; Batubara, Junita (Research Journal in Advanced Humanities, 2026)
Gondang Sabangunan, a traditional musical ensemble of the Toba Batak community, plays an important role in preserving cultural identity, social solidarity, and the philosophy of Dalihan Na Tolu. However, within the urban context of Medan City, the practice of gondang has experienced a shift in meaning from a sacred ritual domain to spaces of entertainment, cultural festivals, and digital media. This transformation creates a dilemma between maintaining authenticity and adapting to modernity, while also revealing a generational gap in cultural understanding. Younger generations tend to be more familiar with global popular culture than with traditional arts, leading to a decline in appreciation for gondang. This study aims to examine the social resonance and transformation of the meaning of Gondang Sabangunan in an urban context and to analyze the role of arts education at SMK Negeri 11 Medan as a strategy for cultural preservation. The research employs a qualitative approach with an ethnographic design, utilizing in-depth interviews, participatory observation, and documentation of gondang practices in the school environment. Data were analyzed thematically using semiotic and sociological approaches, while validity was ensured through triangulation and member checking. The findings reveal that arts education functions as a space for cultural revitalization, a medium for intergenerational value transmission, and an instrument for strengthening local identity resilience. The integration of Gondang Sabangunan into the curriculum not only enhances students’ understanding of cultural heritage but also makes traditional arts relevant to contemporary urban life.